Effects of laser energy density on morphology features and microstructures of the single molten track in selective laser melting - Wang, Sen; Wang, Linzhi; Liu, Jiquan; Yang, Runqi; Li, Jing; Wang, Guoyu (Frontiers in Materials, 2023)
Single molten track (SMT) is the basic unit of the selective laser melting (SLM) process, of which the morphology features and microstructures have great significance on the molding quality. In this study, the effects of laser energy density (LED) on characteristics of SMT were studied with 316L stainless steel. It was found that an optimized range of LED was between 200 and 500 J/mm3, which was the best for SLM process of 316L leading to beautiful SMT appearance such as continuous uniform water-ridge-like surface, good contour straightness, smooth edges, little adhesive powder, and high densification. In addition, when the LED was less than 200 J/mm3, the discontinuous track and concave-convex phenomenon appeared and pore defects can sometimes be seen on surface. When the LED was more than 500 J/mm3, discrete spherical particles showed up on the surface and edge of SMT. The microstructures of the SMT molten pool are mainly composed of equiaxed cellular and columnar dendrites. As the LED decreased, the cellular became smaller and disappeared, while the length and width of columnar crystals even gradually increased. The size of the cellular varies between 0.43 and 1.70 μm with the LEDs increase. The relationship between SMT characteristics and LED found in this work can be readily used to optimize SMT and control the microstructures in situ.